Body Imaging and Sexual Behavior in Lean Women with Polycystic Ovary Syndrome. (23rd August 2013) - Morotti, Elena; Persico, Nicola; Battaglia, Bruno; Fabbri, Raffaella; Meriggiola, Maria Cristina; Venturoli, Stefano; Battaglia, Cesare
Abstract: Introduction: In women with polycystic ovary syndrome (PCOS), changes in body appearance may influence the feminine identity of the patients with possible consequent depression and sexual dysfunction. Aim: The study aims to examine the differences in mood, perceived body image, sexual behavior, and clitoral vascularization between lean PCOS patients and healthy eumenorrheic controls. Methods: Thirty‐three lean PCOS women (Group I) and 22 healthy nonhirsute volunteers (Group II) were submitted, on day 3–5 of the cycle, to ultrasonographic (US) and Doppler analyses, to clinical, hormonal, and biochemical evaluations, and to psychometric tests. Main Outcomes Measures: Main outcome measures are Ferriman–Gallwey score (FG), clitoral volume, clitoral artery Pulsatility Index, the two‐factor Italian McCoy female questionnaire (MFSQ), the Stunkard Figure Rating Scale (FRS), and the Beck Depression Inventory (BDI) questionnaire. Results: The FG score and the androgens resulted, as expected, more elevated in PCOS patients than in controls. However, the US assessment of the clitoral body volume and the resistances registered at the level of the dorsal clitoral artery did not show any difference between Group I and Group II patients. Moreover, the two‐factor Italian MFSQ, the FRS, and the BDI were similar in both groups. Conclusions: It seems that in lean PCOS women, the moderate hirsutism and hyperandrogenism do not have any important influence on body image and self‐esteem and, as a consequence, on sexual function.Morotti E, Persico N, Battaglia B, Fabbri R, Meriggiola MC, Venturoli S, and Battaglia C. Body imaging and sexual behavior in lean women with polycystic ovary syndrome. J Sex Med 2013;10:2752–2760.